Analysis on the situation of subjective well-being and its influencing factors in patients with ankylosing spondylitis. Issue 1 (December 2016) - Wang, Mengmeng; Wang, Sheng; Zhang, Xu; Xia, Qing; Cai, Guoqi; Yang, Xiao; Li, Xiaona; Wang, Li; Xin, Lihong; Xu, Shengqian; Xu, Jianhua; Shuai, Zongwen; et al.
Abstract Background To examine the subjective well-being (SWB) in patients with ankylosing spondylitis (AS) compared with the healthy controls, and to explore the associations between SWB and demographic characteristics, disease-specific variables in AS patients. Methods SWB was assessed with General Well-Being Schedule (GWBS) in 200 AS patients and 210 healthy controls. Comparisons among subgroups were performed to investigate how certain aspects operate as favorable or adverse factors in influencing SWB in the patients with AS. Results Both men and women with AS reported significantly impaired SWB on all scales of the GWBS except for the Control (O) scale. The results revealed that better sleep, lower disease activity and more family care predicted higher SWB. In AS patients, positive attitude towards therapy prospect was significantly associated with higher SWB. Therapy prospect refers to the hope of patients about the disease treatment. Conclusions Compared with general population, SWB might be affected by the onset of AS. There are significant associations between SWB and sleep quality, BASDAI, APGAR, therapy prospect.